Volume 1 2004
DOI: 10.1115/ht-fed2004-56432
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Degradation Effects on Turbulent Flows With Macro-Molecular Polymer Structures

Abstract: Macro-molecular polymer structures due to either the entanglement of polymer molecules or the ionic character of the polymer, have been shown in the literature to enhance the drag reducing abilities of polymer solutions in internal water flows. The purpose of this study is to contrast the performance of an ionic and a non-ionic polymer as drag reduction agents with and without the presence of such macro molecular polymer structures. The endurance of such polymer structures to mechanical degradation is also ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Preparation of the polymer solution is crucial in polymer drag reduction. An extensive study on this issue can be found in Sun Chee Fore et al [22] and Swzalek et al [23]. The process involves de-aeration of filtered tap water to be mixed with the granular polymer and a small concentration of isopropyl alcohol.…”
Section: Facilities Instrumentation and Experimental Proceduresmentioning
confidence: 99%
“…Preparation of the polymer solution is crucial in polymer drag reduction. An extensive study on this issue can be found in Sun Chee Fore et al [22] and Swzalek et al [23]. The process involves de-aeration of filtered tap water to be mixed with the granular polymer and a small concentration of isopropyl alcohol.…”
Section: Facilities Instrumentation and Experimental Proceduresmentioning
confidence: 99%